Delayed Diagnosis of TSH-Secreting Adenoma Attributed to Worsening Post-Traumatic Stress Disorder Symptoms in a Military Veteran Because of Provider Anchoring Bias. Issue 3 (1st March 2017) - Daya, Shyam K.; Paulus, Andrew O.; Braxton, Ernest E.; Vroman, Penny J.; Mathis, Derek A.; Lin, Ryan; True, Mark W.
ABSTRACT: Introduction: Anchoring bias occurs when clinicians hold on to previously known information about a patient, with failure to consider the full realm of possibilities to explain new findings. We present a case of delayed diagnosis of thyroid-stimulating-hormone-secreting pituitary adenoma (TSHoma), a rare disorder, in a military veteran whose symptoms were misconstrued as being caused from worsening of his prior diagnosis of post-traumatic stress disorder (PTSD). Anchoring bias in this case led to 2-year delay in the correct diagnosis. Methods: The clinical, laboratory, radiologic, and pathologic results are presented. Results: We report a case of a 44-year-old retired male Army soldier with a prior diagnosis of PTSD who was evaluated for new symptoms including headaches, blurry vision, palpitations, and anxiety. These symptoms were considered by multiple services as worsening of his PTSD, with acknowledgment of normal thyroid hormone levels from 2 years prior, but with no levels at the time of the new presentation. Attempts to treat with standard PTSD therapies were unsuccessful. When thyroid hormone levels were eventually rechecked 2 years later, he was found to have an inappropriately normal level of thyroid-stimulating hormone (1.9 mcIU/mL) in the setting of elevated free thyroxine (2.30 pg/mL) and free triiodothyronine (5.8 ng/dL). With magnetic resonance imaging revealing a 1.4-cm pituitary macroadenoma, he was diagnosed with a TSHoma. A trial of octreotide, a somatostatin analog, was attempted to shrink the tumor size. However, because of the patient's intolerance of this medication, he underwent endoscopic transsphenoidal surgery as definitive treatment. Pathologic analysis of his tumor was consistent with TSHoma. On various follow-up intervals, he had normalization of thyroid function tests, no evidence of residual tumor on 6-month postoperative imaging, and reported improvement in his symptoms. Conclusion: This case highlights the details of a rare diagnosis of TSHoma, which has an estimated 1 to 2 cases per million in the general population and an unknown prevalence in the military population, in a veteran who had symptoms that were presumed to be worsening PTSD. While understandable to attribute new symptoms to pre-existing diagnoses such as PTSD, clinicians should consider the possibility of alternative diagnoses and perform the routine workup when indicated.